Integrated mutational landscape analysis of endometrial stromal sarcoma - Tobias M. P. Hartwich; Seungji Choi; Ayoung Hwang; Stefania Bellone; Luca Palmieri; Hae Seo; Taekeun Kim; Juhyeon Hong; Camilla Krakstad; Jone Trovik; Ingunn M. Stefansson; Hans Kristian Haugland; et al. (Proceedings of the National Academy of Sciences, 2026)
Endometrial stromal sarcoma (ESS) is a rare uterine malignancy with limited treatment options. We performed integrated whole-genome, whole-exome, and transcriptome sequencing on 80 ESS tumors, comprising 32 low-grade (LG) and 48 high-grade (HG) tumors, to characterize their genetic landscape. The overall mutation burden was modest, with no significant difference between grades; however, we identified six hypermutated cases (7.5%) harboring POLE or mismatch repair mutations, genomic features predictive of immunotherapy response. We identified focal RAD54B amplifications in 15 tumors (18.8%), leading to elevated RAD54B expression and significantly shorter survival. This establishes RAD54B as an oncogenic driver in ESS. Known tumor suppressors (PTEN, TP53) were frequently mutated in HG-ESS but rare in LG-ESS, highlighting distinct grade-specific drivers of malignancy. HG-ESS exhibited widespread chromosomal gains, frequent loss of cell-cycle regulators (RB1, CDKN2A), and numerous private gene fusions arising from complex DNA rearrangements. In contrast, LG-ESS were defined by canonical fusions (e.g., JAZF1–SUZ12 ) and co-occurring deletions in metabolic regulator genes (TSC2, STK11). Finally, in an activating NRAS-mutant (p.Q61R) HG-ESS xenograft, the combination of MEK and FAK inhibition dramatically suppressed tumor growth and prolonged survival, highlighting a promising targeted treatment strategy. Overall, our comprehensive analysis defines the molecular basis of ESS and provides a strong preclinical rationale for precision therapies in this aggressive cancer.